Outbreaks of Bemisia tabaci Mediterranean species in vegetable crops in São Paulo and Paraná States, Brazil - Bello, Vinicius Henrique [UNESP]; Watanabe, Luís Fernando Maranho [UNESP]; Fusco, Lucas MacHado [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Da Silva, Felipe Barreto [UNESP]; Gorayeb, Eduardo Silva [UNESP]; Moura, Mônika Fecury [UNESP]; De Souza, Isabela Morcilo [UNESP]; Muller, Cristiane; Salas, Fernando Javier Sanhueza; Yuki, Valdir Atsushi; Bueno, Regiane Cristina Oliveira De Freitas [UNESP]; et al. (Cambridge University Press (CUP), 2020)
The whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), is one of the most important agricultural pests and virus vectors worldwide. Bemisia tabaci is considered a complex of cryptic species with at least 44 species. Among them, the species Middle East-Asia Minor 1 (MEAM1, formerly B biotype) and Mediterranean (MED, formerly Q biotype) are the most important, and they have attained global status. In Brazil, MEAM1 was first reported in the 1990s and is currently the predominant species in the country, meanwhile, MED was recently reported in the South and Southeast regions and was found to be mainly associated with ornamental plants. Currently, an increasing problem in the management of whitefly infestations in greenhouses associated with bell pepper was observed in São Paulo State, Brazil. The whiteflies were collected and identified based on a microsatellite locus (primer pair BEM23F and BEM23R) and the mitochondrial cytochrome oxidase I gene followed by restriction fragment length polymorphism analysis and sequencing. We observed that MED was the predominant species collected on bell pepper, but it was also found on tomato, cucumber, eggplant, and weeds grown in greenhouses. In open field, we found MED on tomatoes, bell peppers, and eggplants. In addition, MED was identified in Goiás State in association with ornamental plants. The begomovirus Tomato severe rugose virus and the crinivirus Tomato chlorosis virus was detected on bell pepper and tomato, respectively. Only MED specimens were found associated with the virus-infected plants. Moreover, we also investigated the endosymbionts present in the MED whiteflies. The collected populations of B. tabaci MED harbored a diversity of secondary endosymbionts, with Hamiltonella (H) found predominantly in 89 specimens of the 129 tested. These results represent a new concern for Brazilian agriculture, especially for the management of the newly introduced whitefly MED species, which must be implemented to limit the spreading and establishment of this pest in different crops in this country.
Keywords: Bell pepper; cucumber; endosymbionts; Q biotype; tomato; whitefly